a) (x+1) (x^2 - x + 1);
b) (x - 2) (x^2 + 2x + 4);
c) (x - y) (x^2 + xy + y^2);
Va rog dau coroana am mare nevoie de ajutor
Răspunsuri la întrebare
Răspuns de
1
a^3 – b^3 = (a – b)(a^2 + ab + b^2)
a^3 – b^3 = (a – b)(a^2 + ab + b^2)a^3 + b^3 = (a + b)(a^2 – ab + b^2)
a) (x+1)(x^2-x+1)=x^3+1
b) (x-2)(x^2+2x+4)=x^3-2^3=x^3-8
c) (x-y)(x^2+xy+y^2)=x^3-y^3
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă